PENDIDIKAN MORAL DALAM NOVEL SEPATU UNTUK ALMIA KARYA SARA TEE - Della Rostania; Resdianto Permata Raharjo; Titik Indarti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
Moral education is an awareness to support students through skills, knowledge, values ??and attitudes that contribute to social and community life. The purpose of moral education is to create individuals who have a sense of humanity, tolerance, mutual respect and good character. Moral education is closely related to student learning in schools. The teacher, as a student companion at school, plays an important role in the formation of student character. Processing a variety of learning models is one of the areas that must be mastered by teachers. Learning media plays an important role to liven up the learning atmosphere. The purpose of this study is to describe the form of moral education in the novel Shoes for Almia by Sara Tee and to find out the relevance of the novel to learning Indonesian for class IX at the junior high school level. This study uses a qualitative approach with a descriptive method because it describes the forms of moral education in the novel Shoes for Almia by Sara Tee. The data from this research are in the form of narratives and dialogues related to moral education in the novel Shoes for Almia by Sara Tee by reading and taking notes. The data collection technique used is literature study. The results of this study are a form of moral education attitude which includes helping, being friendly, taking a firm stand, sharing, and caring for each other, as well as its relevance to learning Indonesian for class IX at the junior high school level. Keywords: novels, students, learning media, junior high school